Adults' Financial Literacy and Households' Financial Assets: The Role of Banks Information Policies - Margherita Fort; Francesco Manaresi; Serena Trucchi (Center for Economic Studies and ifo Institute (CESifo), 2014)
We investigate the role of banks information policies in fostering the accumulation of financial knowledge. In Italy, banks belonging to the PattiChiari Consortium implement policies aimed at increasing transparency and procedural simplification, without offering services at lower cost with respect to other banks. We exploit this feature of the Italian banking system and show that these policies promote financial literacy. The increase in financial knowledge attributable to banks information policies significantly affects household financial assets. We use these policies as instruments to estimate the effect of financial literacy on financial assets, showing that it is significantly underestimated by OLS correlation.
Keywords: D14; G11; 330; banks information policies; financial assets; financial literacy; instrumental variables